2016
DOI: 10.7202/1034484ar
|View full text |Cite
|
Sign up to set email alerts
|

Les programmes préventifs en milieu scolaire auprès des enfants et des adolescents présentant de l’anxiété

Abstract: L’objectif de cet article est de décrire les programmes de prévention de l’anxiété en milieu scolaire auprès des enfants et des adolescents. Nous rapportons d’abord quelques données sur l’épidémiologie des troubles anxieux, leurs conséquences et les coûts associés afin d’illustrer la pertinence d’intervenir de manière précoce. La section suivante présente le programme Coping Cat, qui a servi d’inspiration aux programmes de prévention. Nous distinguons ensuite les programmes de prévention en milieu scolaire sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 71 publications
1
11
0
2
Order By: Relevance
“…This survey also found that anxiety is more prevalent in girls (22.9%) than in boys (11.8%), and that anxiety increases as students advance into the upper grade levels, although it decreases slightly between secondary 4 (grade 10) and 5 (grade 11). Anxiety has major effects on young people’s lives, as it is associated to an increase in the risk of developing depressive symptoms, suicidal ideation, and drug or alcohol abuse, and a decrease in the ability to concentrate and in academic performance, adaptability, and social skills (Dumas, 2013 ; Turgeon & Gosselin, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This survey also found that anxiety is more prevalent in girls (22.9%) than in boys (11.8%), and that anxiety increases as students advance into the upper grade levels, although it decreases slightly between secondary 4 (grade 10) and 5 (grade 11). Anxiety has major effects on young people’s lives, as it is associated to an increase in the risk of developing depressive symptoms, suicidal ideation, and drug or alcohol abuse, and a decrease in the ability to concentrate and in academic performance, adaptability, and social skills (Dumas, 2013 ; Turgeon & Gosselin, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with those of several previous studies that have described the association between learning disabilities and internalized disorders as close and frequent. Among these studies, we can cite that of Turgeon and Gosselin (2015) who estimated that the risk of having difficulties related to learning to read is tripled in children with anxiety disorders. Our results are also in concordance with the findings of other studies that have found a strong association between anxiety and depressive disorders and academic achievement (Mariage and David, 2001; Kovacs and Goldston, 1991; Blechman et al , 1986; Cole et al , 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the judgments of inefficiency and incompetence in school activities, in front of peers, can lead to manifestations of internalized psychopathological disorders and cause a deterioration in self-esteem among learners with learning difficulties, in general, and reading difficulties in particular. On the other hand, regardless of their initial causes, emotional difficulties can hurt academic success by hindering the cognitive functions (memory, attention, problem resolution) involved in any school learning (Turgeon and Gosselin, 2015). In this case, the negative impact of these disorders is even more accentuated and worsens the situation of children with learning disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…La peur est la réaction émotionnelle face à une menace imminente, qu'elle soit réelle ou perçue, alors que l'anxiété est l'anticipation d'une menace future (APA, 2013). (Donovan et Spence, 2000;Rapee et al, 2005;Turgeon et Gosselin, 2015).…”
Section: Résuméunclassified
“…Le fait de vivre de l'anxiété peut également influencer la façon dont l'élève réalise ce choix de carrière, de manière directe ou indirecte. Les élèves aux prises avec l'anxiété seraient plus susceptibles de s'absenter régulièrement, ce qui a un impact négatif sur leurs résultats académiques et, pour certains d'entre eux, peut mener à décrocher de l'école (Donovan et Spence, 2000;Rapee et al, 2005;Turgeon et Gosselin, 2015). Cela limite alors les options de carrière qui s'offrent à eux, alors que le marché du travail et le système d'éducation québécois sont caractérisés par une augmentation des exigences de formation (Bourdon et Bélisle, 2015).…”
Section: Résuméunclassified